Investigation and treatment of pelvic vein reflux associated with varicose veins: Current views and practice of 100 UK vascular specialists. (February 2020) - Campbell, Bruce; Goodyear, Stephen; Franklin, Ian; Nyamekye, Isaac; Poskitt, Keith
Objective: Management of pelvic vein disorders possibly contributing to leg varicose veins remains variable and controversial. This survey investigated practice in the UK. Methods: Email questionnaire to 328 members of the Vascular Society. Results: One hundred and four (32%) questionnaires were returned. Of 100 respondents treating varicose veins, 9% do not recognise pelvic vein reflux and 11% never investigate or treat it. Indications for investigation include labial (94%) and buttock/upper thigh (70%) varicose veins: 46% use magnetic resonance venography and only 16% transvaginal duplex. Treatments used are coil embolization (89%), sclerotherapy via thigh veins (47%) and transcatheter sclerotherapy (26%). Thirty-four per cent treat only ovarian veins (not internal iliac tributaries). Follow-up is by clinical response (100%): only 14% use duplex. Only 5% treat >10 patients annually. Conclusions: There is substantial variation in the management of pelvic vein reflux in the UK. There is need for further consensus and good clinical trial evidence to guide practice.